THE IMPACT OF AGRICULTURAL PRODUCTIVITY ON RURAL TO URBAN MIGRATION IN JAVA, INDONESIA - Renata Fauzia; Soengwoo Lee (TATALOKA, 2013)
This paper investigates if the improvement of agricultural productivity will decrease rural to urban migration. Since rural to urban migration occurs due mainly to disparity between urban and agricultural wage, we assume that boosting agricultural income will reduce migration to urban areas. It is hypothesized that increase in agricultural productivity would result in a rise in agricultural wage, and hence income, ceteris paribus, reduces rural-urban migration. The data used in this study is the 2010 provincial statistics in West Java, Central Java, and East Java, Indonesia. The agricultural productivity and migration equations were estimated by using Ordinary Least Squares (OLS). The research findings may offer the suggestion to reduce rural to urban migration by boosting rural income through focusing the policy on agricultural productivity. Enhancing investment in agricultural sector such as increasing the number of subsidized fertilizer, adding agricultural labor and livestock, increasing education of rural people, and utilizing agricultural land resource are expected to increase agricultural output.Thus, it would also minimize the wage differential between urban and rural area.